Epidemiology of restless legs syndrome in Turkish adults on the western Black Sea coast of Turkey: A door-to-door study in a rural area - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
Objective: To determine the prevalence and clinical presentation of restless legs syndrome (RLS) in Turk ish population living in Kandira, a town located on the Black Sea coast of Istanbul. Methods: This study was designed as a descriptive, cross-sectional, door-to-door field study. A total of 2111 people aged 18 years and over were selected for the study. The criteria suggested by the IRLSSG (international Restless Legs Syndrome Study Group) were used in the assessment of RLS. All the suspected subjects underwent neurological examination. Results: The prevalence of RLS was found to be 3.4% of Turkish population aged over 18. Female:male ratio was 3.5:1. The prevalence reached peak point (8.3%) in the 58- to 67-year-old group. Prevalence of DM, anemia and polyneuropathy in RLS patients was 13.9%, 8.3% and 4.2%, respectively. Conclusion: RLS prevalence is relatively low, but increases with age in both genders in this Turkish population. Although it has negative effects on daily life, it is not well recognized by the Population. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Restless legs syndrome; Prevalence; Turkey; Severity; Co-morbidity; Rural; PRIMARY-CARE; RISK-FACTORS; PREVALENCE; POPULATION; SYMPTOMS; SLEEP; RLS; ASSOCIATION; DIAGNOSIS